The (In)authenticity of 1 Thessalonians 2.13-16: A Review of Arguments. (October 2019) - Jensen, Matthew
This article critically reviews the arguments for and against the view that 1 Thess. 2.13-16 is a post-Pauline interpolation. It starts with the four arguments that are forwarded to promote the view that it is an interpolation: form-critical/literary, grammatical/syntactical, historical, and theological. After this, a briefer second section outlines the four arguments defending the authenticity of the verses: textual, contextual, traditional, and rhetorical.